Heating pulse tests under constant volume on Boom clay - Lima, A. (2010)
Boom clay formation is a potential natural host rock for geological disposal of high-level nuclear waste in Belgium. Heating pulse tests with controlled power supply (maximum temperature was limited to 85 °C) and controlled hydraulic boundary conditions were performed under nearly constant volume conditions to study the impact of thermal loading on the clay formation. Selected test results of intact borehole samples retrieved in horizontal direction are presented and discussed. The study focuses on the time evolution of temperature and pore water pressure changes along heating and cooling paths, i.e. pore pressure build-up during quasi-undrained heating and later dissipation at constant temperature.